2007
DOI: 10.1029/2006jb004385
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of pyroclastic rocks from Montagne Pelée volcano (Martinique, Lesser Antilles)

Abstract: [1] The hydraulic and electrical properties of pyroclastic rocks have been investigated in laboratory on a representative sampling of Montagne Pelée (Martinique, France) deposits with renewed interest in geophysical applications. This sampling covers all the lithologic units of this volcano: lava dome and lava flows, pumices from ash-andpumice fall and flow deposits, lava blocks from block-and-ash flow and Peléean ''nuées ardentes'' deposits, scoriae from scoria flow deposits. The connected porosity varies ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
47
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 98 publications
(138 reference statements)
5
47
0
1
Order By: Relevance
“…We do however need to consider those data points that have a very similar value of permeability (approximately 3.2 × 10 −17 m 2 , Table 4), with a porosity range of 7.6 to 10.3 vol% that indicate that there is variability of the samples with respect to permeability that may be reflected in the tortuosity of the porous network. This is consistent with the findings of Bernard et al (2007) and Heap et al (2014) such that the permeability in volcanic rocks is highly dependent upon connectivity of the microstructure. With respect to microstructure, we have shown that the porosity is very closely linked to crack surface area ( Figure 8D) and, thus, that increasing crack density corresponds to a sample with a higher permeability.…”
Section: Permeability and Porositysupporting
confidence: 81%
See 1 more Smart Citation
“…We do however need to consider those data points that have a very similar value of permeability (approximately 3.2 × 10 −17 m 2 , Table 4), with a porosity range of 7.6 to 10.3 vol% that indicate that there is variability of the samples with respect to permeability that may be reflected in the tortuosity of the porous network. This is consistent with the findings of Bernard et al (2007) and Heap et al (2014) such that the permeability in volcanic rocks is highly dependent upon connectivity of the microstructure. With respect to microstructure, we have shown that the porosity is very closely linked to crack surface area ( Figure 8D) and, thus, that increasing crack density corresponds to a sample with a higher permeability.…”
Section: Permeability and Porositysupporting
confidence: 81%
“…Forms of the KozenyCarman relation have previously been used in the study of volcanic rocks (e.g., Saar and Manga 1999;Costa 2006;Bernard et al 2007;Heap et al 2014), while others have used a heavily simplified version (e.g., Rust et al 2003;Mueller et al 2005;Lavallée et al 2013). The Kozeny-Carman relation is of the form:…”
Section: Permeability Modelingmentioning
confidence: 99%
“…By contrast, numerous room temperature permeability measurements have been reported for extrusive volcanic rocks such as lava blocks from Mt. Pelee, Colima, and Unzen (e.g., Bernard et al 2007;Heap et al 2015;Kendrick et al 2013;Mueller et al 2005). Additionally, a handful of studies have assessed the temporal changes in the permeability of hydrothermal systems at constant temperatures (Moore et al 1994;Morrow et al 2001) or under combined high pressure and temperature conditions (30 to 150 MPa and up to 600°C) (Zharikov et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Manga 1999; Polacci et al 2003;Rust et al 2003;Rosi et al 2004;Mueller et al 2005;Gualda and Rivers 2006;Wright et al 2006;Bernard et al 2007; Bouvet de Maisonneuve et al 2008).…”
unclassified